3D Cell-centered hydrodynamics with subscale closure model and multi-material remap. (15th July 2020) - Chiravalle, Vincent P.; Barlow, Andrew; Morgan, Nathaniel R.
Highlights: A cell-centered ALE method using a multidirectional approximate Riemann solution. Quadratic polynomial reconstructions of velocity and stress. ALE method with interface-aware subscale closure model and multi-material remap. First study to evaluate the interface aware closure model on 3D Eulerian meshes. A suite of 3D multi-material test problems including both gas and solid dynamics. Abstract: We extend a higher-order finite volume cell-centered hydrodynamic (CCH) formulation to include an interface-aware subscale closure model and a multi-material remap for simulating 3D compressible hydrodynamic problems within an arbitrary Lagrangian-Eulerian (ALE) framework. This CCH formulation involves a multidirectional approximate Riemann solution using quadratic polynomial reconstructions of the stress tensor and the velocity. At the subscale level, we determine pair-wise material interactions by solving a distinct approximate Riemann problem at the common interface, using the volume of fluids (VOF) method to find the interface. Material interactions are constrained to ensure smooth pressure equilibration among materials. The accuracy and robustness of the ALE method is demonstrated by simulating a suite of 3D Cartesian multi-material problems covering both gas and solid dynamics, where each test case has two or more materials.